Strategic Waiting for Consumer-Generated Quality Information: Dynamic Pricing of New Experience Goods - Yu, Man; Debo, Laurens; Kapuscinski, Roman (Management Science, 2016)
In this paper, we study the impact of consumer-generated quality information (e.g., consumer reviews) on a firm’s dynamic pricing strategy in the presence of strategic consumers. Such information is useful, not only to the consumers that have not yet purchased the product but also to the firm. The informativeness of the consumer-generated quality information depends, however, on the volume of consumers who share their opinions and, thus, depends on the initial sales volume. Hence, via its initial price, the firm not only influences its revenue but also controls the quality information flow over time. The firm may either enhance or dampen the quality information flow via increasing or decreasing initial sales. The corresponding pricing strategy to steer the quality information flow is not always intuitive. Compared to the case without consumer-generated quality information, the firm may reduce the initial sales and lower the initial price. Interestingly, the firm may get strictly worse off due to the consumer-generated quality information. Even when the firm benefits from consumer-generated quality information, it may prefer less accurate information. Consumer surplus can also decrease due to the consumer-generated quality information, contrary to the conventional wisdom that word of mouth should help consumers. We examine extensions of our model that incorporate capacity investment, firm’s private information about quality, alternative updating mechanisms, as well as multiple sales periods, and show that our insights are robust. This paper was accepted by Yossi Aviv, operations management.